Certain flexibilities in land-use plans Towards a method for assessing flexibility. (May 2020) - Van den Hoek, Duncan; Spit, Tejo; Hartmann, Thomas
Highlights: There exists a relationship between flexibility and legal certainty but this is not per definition negatively correlated. Both procedural and material certainty affect this relationship. Land-use plans are central planning instruments wherein this relationship is put in practice and guides activities and societies. A method is drafted to determine the amount of flexibility derived from a land-use plan for a specific planning system. This method can determine the amount of flexibility for a large amount of land-use plans in an uniform matter. Abstract: The trade-off between flexibility and legal certainty is inherent in every planning system. This trade-off is especially apparent within a land-use plan. Flexibility and legal certainty are often seen as communicating vessels: the demise of one leads to an increase in the other. Within land-use plans, however, the connection between the two is more subtle. For a land-use plan, the choice between being specific or open, and rigid or adaptable, determine the amount of flexibility. With these choices a land-use plan can increase its flexibility without decreasing legal certainty. Within reason the legal certainty can even benefit from more flexibility. However, current academic literature lacks a structured way to analyse flexibility contained within a land-use plan. Such a method is necessary for analysing and comparing different land-use plans. This paper will provide such a method and analyse thirteen different land-use plans in the Netherlands on their flexibility. It will show that a structured method can prove to be useful for analysing and comparing different land-use plans. The research provides insight into the complex balance between flexibility and legal certainty and presents an assessment tool which can be used for further academic research.